Going Along to Get Along: Diplomatic Pressure and Interstate Socialization at the United Nations - Al-Mulla, Naif (Diplomatic Studies, 2025)
Going Along to Get Along: Diplomatic Pressure and Interstate Socialization by Naif Al-Mulla explores how diplomatic pressure shapes global governance at the United Nations. Through rigorous analysis and empirical examples, the book demonstrates how diplomatic pressure influences foreign policy positions and, by extension, global, multilateral outcomes. The work challenges assumptions and provides fresh insight, showcasing the cumulative effect of proactive diplomacy. Ideal for postgraduates, scholars, and policymakers, it offers a comprehensive understanding of how interstate coalitions can strategically mobilize diplomatic pressure to gain wide acceptance of a cause, with far-reaching implications from the United Nations to capitals worldwide.